The effects of cycling cleat position on subsequent running performance in a simulated duathlon - Paton, C. D.; Jardine, T. (Journal of Science and Cycling, 2012)
Strategies that reduce the physiological load during the cycling phase of triathlon events may enable athletes to perform better during the subsequent running phase. The current study examines the effects of changes in shoe cleat position, during the cycling phase of a simulated duathlon, on running performance of competitive triathletes. Controlled crossover. 12 triathletes completed a simulated duathlon race using either their normal (control) cycling cleat position or an experimental mid-foot (arch) shoe cleat position. The duathlon consisted of a 30-min cycle, completed at 65% of the athlete`s previously determined peak aerobic power output, followed by a self-paced maximal effort 5.5-km treadmill run. Respiratory-gas measurements were made throughout testing using an automated online metabolic system. There were only trivial differences between conditions for any metabolic variables obtained during the cycling phase of the duathlon. However run time following the mid-foot condition was 2.2% (90% CI 0.8-3.6%) shorter compared to the control condition. In addition Oxygen consumption during the run phase was greater following the mid-foot condition by 2.2% (-0.5-5.1%). We conclude that worthwhile performance gains can be achieved during the running phase of a duathlon when athletes utilize a mid-foot-cleat shoe position during the cycling phase of an event. The improvement in running performance was likely due to a reduction in the rate of plantar flexor muscle fatigue during the cycling phase of the event.